Wybór obiektywnej niepewności jako postawa filozofii egzystencji. Soren Kierkegaard i Odo Marquard (Choosing Objective Uncertainty as an Attitude of Existential Philosophy. Soren Kierkegaard and Odo Marquard) - Dominika Boroń (Analiza i Egzystencja, 2011)
The idea of the article is to search for the roots of the so-called existential thinking, using the peculiar comparison: of the religiously oriented ideas of Kierkegaard ( especially his notions of subjective and objective thinker and the idea of subjective truth)and contemporary ideas of Odo Marquard’s hermeneutical skepticism. Surprisingly, Marquard’s anthropologically and sociologically oriented reflection, while dealing with the problem of human search for absolute knowledge and its depreciation of particular existence, comes to much the same reflections as Kierkegaard: stating rational inability to reach The Objective. Both philosophers analyze the dynamics of the thinking subject and come to more similar statements: Kierkegaard’s notion of objective uncertainty can be, to the certain extent, used to describe attitude of modern thinker described by Marquard. “To the certain extent” – because it is hard and not legitimized to avoid in interpretation the ultimate religious goal that ties up the whole Kierkegaard’s authorship and makes his thought so specific. But the similarities are not meant just to be shown here: they aim to point out certain, very substantial reflection that lies at the root of the existential thinking and makes it still necessary. It is the reflection that sees human mortality, individuality and the dynamic character of the self as the basis for giving primacy in philosophy to the “here and now” questions of how to live and die and how to share those questions with others.